Kazakh proper names in English translation: variability and risks of non-standardized usage of computer-assisted translation tools - Zadorozhnaya, L.A.; Kutpanova , A.A.; Badaliyev, A.M. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The present study is dedicated to the analysis of the variability of Kazakh proper names, as well as the challenging tasks that arise from the non-standardized usage of computer-assisted translation tools. The authors of the research conducted a translation experiment based on a two-stage survey of respondents whose professional activities are connected with linguistics and translation. The survey was designed based on a thorough analysis of theoretical sources on various aspects of onomastics and digital technologies in translation. In the course of the research, extralinguistic issues were given consideration, including the trend of digitalization and the transition of the Kazakh language in the Republic of Kazakhstan to Latin script. The methodology of the research is based on the hypothesis of an interconnection between a high percentage of variability of Kazakh proper names in English translation and non-standardized usage of computer-assisted translation tools, as well as neural networks. The authors draw conclusions about the application of an interdisciplinary approach to the solution of relevant tasks of onomastics in the context of the theory and practice of translation.